Techno-economic analysis of the process for obtaining Bioethanol from rice husks and whey - Laborde, María Fernanda; Capdevila, Veronica Elisabeth; Ponce-Ortega, José María; Gely, María Cristina; Pagano, Ana María (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2022)
This work proposes a novel integrated process for second-generation bioethanol production with an approach simulated in Aspen HYSYS®. Rice husk and dairy whey were used to revalorize for this bioprocess. The energy recovery of the bioprocess was optimized using the Pinch method; savings of 45.45% and 100% were obtained for heating and cooling utilities, respectively, concerning the process without a heat exchange network (HEN). It was possible to compare the costs of mutually exclusive alternatives between the process alternatives with andwithout HEN. The capital investment with HEN was similar to the process without HEN. Instead, savings by 77.8% of utility costs per year was found in the process with HEN. A differential cash flow for ten years was generated, and a positive differential net present value (NPV) was determined. Therefore, HEN is an economically convenient and environmentally friendly option since energy consumption reduction canminimize environmental damage.